Párizs és a délszláv állam születése - Majoros, István (Közép-Európai Közlemények, 2011)
The study presents the role of France in the birth of the Jugoslave state during the World War I. The relations date back to the 16th century between the Balkans belonging to the Ottoman Empire counterbalancing the Habsburg Monarchy and France. At the end of the 19th century we can see French investisments in the Serbian economy and some years before the World War I the economical relations became stronger between the two countries. After the defeat France helped the Serbian army to escape from the Balkans to Corfu, Bizerta and Thessaloniki and the Serbian army took parts in the military operations of the Allied Forces of Balkans under the command of Sarrail and Franchet d’Esperay and the main goal of the French policy was to liberate Serbia. At the end of the World War I the Balkans became strategical region for Paris that’s why the Serbian efforts to unite the Jugoslave people were supported by the French policy. But at the same time the Jugoslave efforts and the Italian goals in the Balkans caused political tensions and a delicate situation for France. In spite of this Paris supported the creation of the new Jugoslave state under Serbian domination. The study presents the French policy during the World War I, the activity of the French minister, Fontenay in Belgrade and the French slavistes working in the favour of the Jugoslave unity.